Comparative evaluation of deltamethrin concentration and exposure time-dependent susceptibility in pyrethroid resistant and susceptible populations of three major stored product insect pests - Çetin Mutlu; Jacqueline Abarca-Duran; William R. Morrison; Kun Yan Zhu; Georgina V. Bingham (Crop Protection, 2026)

Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Influence of commodity type and temperature on the population growth of Trogoderma granarium Everts and Trogoderma variabile Ballion (Coleoptera: Dermestidae) - Georgia V. Baliota; William R. Morrison; Michael J. Domingue; Christos G. Athanassiou (Journal of Stored Products Research, 2026)

Computational Modeling of Bridging Vein Rupture and Acute Subdural Hematoma Growth - Delin Zeng; Andrew V. Basilio; Toshiyuki Yanaoka; Leanne A. Pichay; Gerard A. Ateshian; Steve A. Maas; Barclay Morrison (Annals of Biomedical Engineering, 2025)

Efficacy of amorphous silica dust for use against Sitophilus granarius and Rhyzopertha dominica as a grain protectant - Hannah E. Quellhorst; Maria K. Sakka; Georgia V. Baliota; Christos G. Athanassiou; Kun Yan Zhu; William R. Morrison (Journal of Stored Products Research, 2025)

A synergist increases short-term efficacy of long-lasting insecticide-incorporated netting against pyrethroid-resistant maize weevil, Sitophilus zeamais - Sabita Ranabhat; Hannah E. Quellhorst; Brandon Black; Jaycob Andersen; Breck Aguinaga; Matthew C. Hetherington; Georgina V. Bingham; Kun Yan Zhu; William R. Morrison (Journal of Pest Science, 2025)

Classification of direct threats to the conservation of ecosystems and species 4.0 - Nick Salafsky; Claire Relton; Bruce E. Young; Philippe Lamarre; Monika Böhm; Maxime Chénier; Erica Cochrane; Mark Dionne; Kevin K. He; Craig Hilton‐Taylor; Charles Latrémouille; John Morrison; et al. (Conservation Biology, 2025)
Identifying and assessing the magnitude of direct threats to ecosystems and species are critical steps to prioritizing, planning, implementing, and assessing conservation actions. Just as medical clinicians and researchers need a standard way to talk about human diseases, conservation practitioners and scientists need a common and comprehensive language to talk about the threats they are facing to facilitate joint action, evaluation, and learning. To meet this need, in 2008 the IUCN Species Survival Commission and the Conservation Measures Partnership produced the first version of a common threats classification with the understanding that it would be periodically updated to take into account new information and learning. We present version 4.0 of this classification. For this latest update, we reviewed existing versions and derivatives of the original classification, over 1000 citations of the classification, threats data from over 2900 real‐world conservation projects, and comments from many users. Based on our findings, we made changes to the threats classification scheme, including addition of a level 0 threat class, refinement of levels 1 and 2 threat categories, and addition of the threat “Fencing & walls” to level 2. Also added were level 3 threat types and modifiers that provide a more detailed description of different types of direct threats and thus allow users to fine‐tune analyses and actions. The update also clarifies how to treat various stressors, including natural disaster events and climate change. As a result of these changes, we revised the formal definition of direct threats. They include human actions that are the direct cause of ecosystem or species‐population degradation and loss, such as agriculture, transport, natural resource use, and ecosystem management. They also include ultimate stressors in natural systems whose dynamics have been altered by the effects of current or historical human actions, such as invasive or problematic native species, pollution, natural disasters, and climate change.

Spillage and food dust do not decrease efficacy of long-lasting insecticide-incorporated netting against stored product insects - Sabita Ranabhat; Çetin Mutlu; Georgina V. Bingham; Jennifer Abshire; Tanja McKay; Kun Yan Zhu; William R. Morrison (Journal of Stored Products Research, 2025)

Experimental Measurement and Mathematical Quantification of Fixed-Charged Density in Rat and Pig Brain Tissue - Delin Zeng; Andrew V. Basilio; Leanne A. Pichay; Gerard A. Ateshian; Olivia S. Hansen; Alexander Romanov; Barclay Morrison (Annals of Biomedical Engineering, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Sex-linked differences in semiochemical-mediated movement by Trogoderma variabile Ballion and Trogoderma inclusum LeConte (Coleoptera: Dermestidae) after exposure to long-lasting insecticide-incorporated netting - Sabita Ranabhat; Michael J. Domingue; Ian Stoll; Georgina V. Bingham; Kun Yan Zhu; William R. Morrison (Journal of Stored Products Research, 2024)

Nitrous oxide and methane fluxes from plasma-treated pig slurry applied to winter wheat - I. L. Lloyd; R. P. Grayson; M. V. Galdos; R. Morrison; P. J. Chapman (Nutrient Cycling in Agroecosystems, 2024)
The use of livestock waste as an organic fertiliser releases significant greenhouse gas emissions, exacerbating climate change. Innovative fertiliser management practices, such as treating slurry with plasma induction, have the potential to reduce losses of carbon and nitrogen to the environment. The existing research on the effectiveness of plasma-treated slurry at reducing nitrous oxide (N 2 O) and methane (CH 4 ) emissions, however, is not comprehensive, although must be understood if this technology is to be utilised on a large scale. A randomised block experiment was conducted to measure soil fluxes of N 2 O and CH 4 from winter wheat every two hours over an 83-day period using automated chambers. Three treatments receiving a similar amount of plant-available N were used: (1) inorganic fertiliser (IF); (2) pig slurry combined with inorganic fertiliser (PS); (3) plasma-treated pig slurry combined with inorganic fertiliser (TPS). Cumulative N 2 O fluxes from TPS (1.14 g N m −2 ) were greater than those from PS (0.32 g N m −2 ) and IF (0.13 g N m −2 ). A diurnal pattern in N 2 O fluxes was observed towards the end of the experiment for all treatments, and was driven by increases in water-filled pore space and photosynthetically active radiation and decreases in air temperature. Cumulative CH 4 fluxes from PS (3.2 g C m −2 ) were considerably greater than those from IF (− 1.4 g C m −2 ) and TPS (− 1.4 g C m −2 ). The greenhouse gas intensity of TPS (0.2 g CO 2 -eq kg grain −1 ) was over twice that of PS (0.07 g CO 2 -eq kg grain −1 ) and around six times that of IF (0.03 g CO 2 -eq kg grain −1 ). Although treating pig slurry with plasma induction considerably reduced CH 4 fluxes from soil, it increased N 2 O emissions, resulting in higher non-CO 2 emissions from this treatment. Life-cycle analysis will be required to evaluate whether the upstream manufacturing and transport emissions associated with inorganic fertiliser usage are outweighed by the emissions observed following the application of treated pig slurry to soil.

Simulating Cerebral Edema and Ischemia After Traumatic Acute Subdural Hematoma Using Triphasic Swelling Biomechanics - Andrew V. Basilio; Delin Zeng; Leanne A. Pichay; Gerard A. Ateshian; Peng Xu; Steve A. Maas; Barclay Morrison (Annals of Biomedical Engineering, 2024)

Editorial: Contemporary marine science, its utility and influence on regulation and government policy - Piers Larcombe; Angus Morrison-Saunders; Peter V. Ridd (Frontiers in Marine Science, 2024)

Region-Dependent Mechanical Properties of Human Brain Tissue Under Large Deformations Using Inverse Finite Element Modeling - Andrew V. Basilio; Delin Zeng; Leanne A. Pichay; Steve A. Maas; Sowmya N. Sundaresh; John D. Finan; Benjamin S. Elkin; Guy M. McKhann; Gerard A. Ateshian; Barclay Morrison (Annals of Biomedical Engineering, 2024)

How long have we been mistaken? Multi-tools shedding light into the systematics of the widespread deep-water genus Madrepora Linnaeus, 1758 (Scleractinia) - Kátia C.C. Capel; Carla Zilberberg; Raphael M. Carpes; Cheryl L. Morrison; Claudia F. Vaga; Andrea M. Quattrini; Randolph ZB Quek; Danwei Huang; Stephen D. Cairns; Marcelo V. Kitahara (Molecular Phylogenetics and Evolution, 2024)

First detection and complete genome sequence of a new potexvirus naturally infecting Adenium obesum - Marie-Emilie A. Gauthier; Shamila W. Abeynayake; Ruvini V. Lelwala; Cassie A. McMaster; Robin Eichner; Jennifer Morrison; Candace E. Elliott; Sonia Fiorito; Adrian Dinsdale; Julie Pattemore; Roberto A. Barrero (Archives of Virology, 2023)
Here, we report the detection and complete genome sequence of a novel potexvirus, tentatively named “Adenium obesum virus X” (AobVX), isolated from Adenium obesum , that was sent for virus screening at Australian Government post-entry quarantine (PEQ) facilities after being imported into Australia from China. The AobVX genome is 6781 nucleotides in length excluding the poly(A) tail and is predicted to encode conserved potexvirus proteins and sequence motifs across five open reading frames. The RNA-dependent RNA polymerase of this virus shares the highest amino acid sequence similarity with that of nerine potexvirus 1 (58.7% identity) and nerine virus X (58.58% identity). This is the first report of a positive-sense single-stranded RNA virus in A. obesum related to members of the genus Potexvirus in the family Alphaflexiviridae.

Different trap designs and attractants affect the capture of multiple life stages of Trogoderma granarium Everts and Trogoderma variabile Ballion in the laboratory - Maria K. Sakka; Marina Gourgouta; William R. Morrison; Michael J. Domingue; Robert F. Grosdidier; Rachel V. Wilkins; Christos G. Athanassiou (Journal of Stored Products Research, 2023)

Editorial on the FDA Report on “Successes and Opportunities in Modeling & Simulation for FDA” - Kausar B. Riaz Ahmed; Pras Pathmanathan; Shruti V. Kabadi; Tomas Drgon; Tina M. Morrison (Annals of Biomedical Engineering, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Region-Dependent Viscoelastic Properties of Human Brain Tissue Under Large Deformations - Sowmya N. Sundaresh; John D. Finan; Benjamin S. Elkin; Andrew V. Basilio; Guy M. McKhann; Barclay Morrison (Annals of Biomedical Engineering, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Temporary threshold shift after noise exposure in hypobaric hypoxia at high altitude: results of the ADEMED expedition 2011 - K. Fehrenbacher; C. Apel; D. Bertsch; M. S. van der Giet; S. van der Giet; M. Grass; C. Gschwandtl; N. Heussen; N. Hundt; C. Kühn; A. Morrison; M. Müller-Ost; et al. (International Archives of Occupational and Environmental Health, 2021)
Objectives To evaluate whether there is an increased risk for noise-induced hearing loss at high altitude rsp. in hypobaric hypoxia. Methods Thirteen volunteers got standard audiometry at 125, 250, 500, 750, 1000, 1500, 2000, 3000, 4000, 6000, and 8000 Hz before and after 10 min of white noise at 90 dB. The system was calibrated for the respective altitude. Measurements were performed at Kathmandu (1400 m) and at Gorak Shep (5300 m) (Solo Khumbu/Nepal) after 10 days of acclimatization while on trek. Temporary threshold shift (TTS) was analyzed by descriptive statistics and by factor analysis. Results TTS is significantly more pronounced at high altitudes. Acclimatization does not provide any protection of the inner ear, although it increases arterial oxygen saturation. Conclusion The thresholds beyond which noise protection is recommended (> 80 dB) or necessary (> 85 dB) are not sufficient at high altitudes. We suggest providing protective devices above an altitude of 1500 m (“ear threshold altitude”) when noise level is higher than 75 dB and using them definitively above 80 dB. This takes the individual reaction on hypobaric hypoxia at high altitude into account.

Export of photolabile and photoprimable dissolved organic carbon from the Connecticut River - Byungman Yoon; Jacob D. Hosen; Ethan D. Kyzivat; Jennifer H. Fair; Lisa C. Weber; Kelly S. Aho; Rachel Lowenthal; Serena Matt; William V. Sobczak; Jamie B. Shanley; Jon Morrison; James E. Saiers; et al. (Aquatic Sciences, 2021)

Review of infectious agent occurrence in wild salmonids in British Columbia, Canada - Beibei Jia; Marina K. V. C. Delphino; Babafela Awosile; Tim Hewison; Patrick Whittaker; Diane Morrison; Mykolas Kamaitis; Ahmed Siah; Barry Milligan; Stewart C. Johnson; Ian A. Gardner (Journal of Fish Diseases, 2020)
Wild Pacific salmonids (WPS) are economically and culturally important to the Pacific North region. Most recently, some populations of WPS have been in decline. Of hypothesized factors contributing to the decline, infectious agents have been postulated to increase the risk of mortality in Pacific salmon. We present a literature review of both published journal and unpublished data to describe the distribution of infectious agents reported in wild Pacific salmonid populations in British Columbia (BC), Canada. We targeted 10 infectious agents, considered to potentially cause severe economic losses in Atlantic salmon or be of conservation concern for wild salmon in BC. The findings indicated a low frequency of infectious hematopoietic necrosis virus, piscine orthoreovirus, viral haemorrhagic septicaemia virus, Aeromonas salmonicida , Renibacterium salmoninarum , Piscirickettsia salmonis and other Rickettsia‐like organisms, Yersinia ruckeri , Tenacibaculum maritimum and Moritella viscosa . No positive results were reported for infestations with Paramoeba perurans in peer‐reviewed papers and the DFO Fish Pathology Program database. This review synthesizes existing information, as well as gaps therein, that can support the design and implementation of a long‐term surveillance programme of infectious agents in wild salmonids in BC.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Growth and reproductive characteristics of rarely observed resident female Dolly Varden (Salvelinus malma malma) in North America - Colin P. Gallagher; Christie M. Morrison; Ellen V. Lea; Norman M. Halden; Kimberly L. Howland (Hydrobiologia, 2019)

Merlin modulates process outgrowth and synaptogenesis in the cerebellum - A. Toledo; F. Lang; M. Doengi; H. Morrison; V. Stein; S. L. Baader (Brain Structure and Function, 2019)

Differential Proteomics for Distinguishing Ischemic Stroke from Controls: a Pilot Study of the SpecTRA Project - A. M. Penn; V. Saly; A. Trivedi; M. L. Lesperance; K. Votova; A. M. Jackson; N.S. Croteau; R. F. Balshaw; M. B. Bibok; D. S. Smith; K. K. Lam; J. Morrison; et al. (Translational Stroke Research, 2018)

A Case Study of Turbulence in the Nocturnal Boundary Layer During the Indian Summer Monsoon - Pramit Kumar Deb Burman; Thara V. Prabha; Ross Morrison; Anandakumar Karipot (Boundary-Layer Meteorology, 2018)

Correction to: Genetic and morphological sex identification methods reveal a male-biased sex ratio in the Ivory Gull Pagophila eburnea - Glenn Yannic; Thomas Broquet; Hallvard Strøm; Adrian Aebischer; Christophe Dufresnes; Maria V. Gavrilo; H. Grant Gilchrist; Mark L. Mallory; R. I. Guy Morrison; Brigitte Sabard; Roberto Sermier; Olivier Gilg (Journal of Ornithology, 2018)

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

Genetic and morphological sex identification methods reveal a male-biased sex ratio in the Ivory Gull Pagophila eburnea - Glenn Yannic; Thomas Broquet; Hallvard Strøm; Adrian Aebischer; Christophe Dufresnes; Maria V. Gavrilo; H. Grant Gilchrist; Mark L. Mallory; R. I. Guy Morrison; Brigitte Sabard; Roberto Sermier; Olivier Gilg (Journal of Ornithology, 2016)

High connectivity in a long-lived high-Arctic seabird, the ivory gull Pagophila eburnea - Glenn Yannic; Jonathan M. Yearsley; Roberto Sermier; Christophe Dufresnes; Olivier Gilg; Adrian Aebischer; Maria V. Gavrilo; Hallvard Strøm; Mark L. Mallory; R. I. Guy Morrison; H. Grant Gilchrist; Thomas Broquet (Polar Biology, 2016)

Reconstruction of recurrent synaptic connectivity of thousands of neurons from simulated spiking activity - Yury V. Zaytsev; Abigail Morrison; Moritz Deger (Journal of Computational Neuroscience, 2015)

Workload during cardiopulmonary resuscitation - T. Küpper; J. Steffgen; A. Morrison; J. Milledge; V. Schöffl (International Archives of Occupational and Environmental Health, 2015)

Overexpression of α2,3sialyl T-antigen in breast cancer determined by miniaturized glycosyltransferase assays and confirmed using tissue microarray immunohistochemical analysis - Shilpa A. Patil; Wiam Bshara; Carl Morrison; E. V. Chandrasekaran; Khushi L. Matta; Sriram Neelamegham (Glycoconjugate Journal, 2014)

Winter weather versus group thermoregulation: what determines survival in hibernating mammals? - V. P. Patil; S. F. Morrison; T. J. Karels; D. S. Hik (Oecologia, 2013)

Cold-water event of January 2010 results in catastrophic benthic mortality on patch reefs in the Florida Keys - M. A. Colella; R. R. Ruzicka; J. A. Kidney; J. M. Morrison; V. B. Brinkhuis (Coral Reefs, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Multicenter retrospective development and validation of a clinical prediction rule for nosocomial invasive candidiasis in the intensive care setting - L. Ostrosky-Zeichner; C. Sable; J. Sobel; B. D. Alexander; G. Donowitz; V. Kan; C. A. Kauffman; D. Kett; R. A. Larsen; V. Morrison; M. Nucci; P. G. Pappas; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Metabolic correlates of leg length in breeding arctic shorebirds: the cost of getting high - Ralph V. Cartar; R. I. Guy Morrison (Journal of Biogeography, 2005)
Aim We test the hypothesis that tarsus length in all shorebirds breeding in the Canadian arctic shows an evolutionary response to average metabolic stress encountered across the breeding range, such that birds nesting in metabolically stressful environments have relatively shorter legs. Longer‐legged birds living in colder environments will experience greater metabolic costs because their torsos are elevated farther away from the ground's wind‐dampening boundary layer. Methods We use weather data (temperature, wind speed, global solar radiation) from 27 arctic weather stations measured over 37 years, and a previously published model of heat transfer, to characterize the metabolic harshness over the breeding season of the ranges of each of the 17 shorebirds of the family Charadriidae nesting in the Canadian arctic. Results After controlling for the lengths of two other body extremities (wing and bill), there was a significant negative relationship between tarsus length and mean metabolic harshness. This result was obtained whether species were treated as independent data points, or in a comparative analysis using standardized independent contrasts. Main conclusions We support a unique extension of Allen's rule: body‐supporting appendages of homeotherms may be shorter in colder environments so as to take advantage of a boundary layer effect, thereby reducing metabolic costs.

Beyond Noah: Saving Species Is Not Enough - JONATHAN V. HIGGINS; TAYLOR H. RICKETTS; JEFFREY D. PARRISH; ERIC DINERSTEIN; GEORGE POWELL; SUZANNE PALMINTERI; JONATHAN M. HOEKSTRA; JOHN MORRISON; ADAM TOMASEK; JONATHAN ADAMS (Conservation Biology, 2004)

Egg Shell Architecture of the Stink Bug, Eocanthecona furcellata (Wolff.): Ultrastructure of Micropylar Processes and Egg Burster - Vineet Kumar; M. N. Morrison; A. M. Babu; V. Thiagarajan (International Journal of Tropical Insect Science, 2002)

Marine Boundary-Layer Variability Over The Indian Ocean During Indoex (1998) - Vijayakumar Manghnani; Sethu Raman; Devdutta S. Niyogi; Vinayaka Parameswara; John M. Morrison; S. V. Ramana; J. V. S. S. Raju (Boundary-Layer Meteorology, 2000)

Non-Markov negative correlation between interspike intervals in mammalian sympathetic efferent discharges - K. Floyd; Verity E. Hick; A. V. Holden; Juthika Koley; J. F. B. Morrison (Biological Cybernetics, 1982)